Motivation and Incentives in an Online Labor Market - Sebastian Fest; Ola Kvaloy; Petra Nieken; Anja Schöttner (ZBW - Leibniz Information Centre for Economics, 2020)
An increasing number of workers participate in online labor markets. In contrast to traditional employment relationships within firms, the interaction between online workers and their employers are short and impersonal, which makes motivating online workers more challenging. We present results from two large-scale real-effort experiments on Amazon Mechanical Turk investigating the effects of monetary and non-monetary motivational instruments. In the first experiment, we study the effects of performance pay and simple upfront messages (praise or reference points) on performance. The second experiment concentrates on the effects of communication techniques used by charismatic leaders. Performance pay increases output significantly. Sending simple messages, however, can have a significantly negative effect on output. The results from the second experiment show that charismatic communication techniques can also backfire when only a subset of them is used, whereas using a broad set including quantitative goals increases output significantly. Neither intervention had any effect on the quality of work.
Keywords: C93; M52; J33; 330; Online Labor Market; Performance Pay; Motivation; Charismatic Leadership